Inductor Design for a High Performance Dc-Dc Modular Multilevel Converter - Rojas-Lobos, F; Diaz-Diaz, M; Cerda-Jimenez, C; Droguett-Olea, G (Institute of Electrical and Electronics Engineers Inc., 2019)
In this paper is presented a simple method to design an inductor for high performance on a DC-DC Modular Multilevel Converter(MMC). This element is one of the main limitations for a proper fulfilment. A high-frequency inductor for high power applications is a key element to achieve high efficiency in such type of converters. The theoretical design of the inductor is compared with an experimental prototype, which is then implemented in a high-power DC-DC converter. Experimental results validate the accuracy of the theoretical design and the improvements in the efficiency of the overall DC-DC high power converter. © 2019 IEEE.